Anti-3-Hydroxy-3-Methylglutaryl-Coenzyme A Reductase Immune-Mediated Necrotizing Myopathy following mRNA SARS-CoV-2 Vaccination - Marta Rodrigues de Carvalho; Myrian Mathildes Sá de Deus Rocha; Vinícius Alves Bezerra; Maciel Eduardo de Pontes; Maria Cristina del Negro; Julio Salgado Antunes; Vinícius Viana Abreu Montanaro; Rubens Nelson Morato Fernandez (Case Reports in Neurological Medicine)
The new coronavirus (COVID-19) pandemic has resulted in the unprecedented production of vaccines. In this context, the possible adverse effects remain to be identified and reported. In this article, we report the case of a young female patient who developed anti-3-hydroxy-3-methylglutaryl-coenzyme A reductase (anti-HMG-CoA) immune-mediated necrotizing myositis (IMNM) after receiving the Pfizer-BioNTech (BNT162b2) COVID-19 vaccine. The diagnosis of probable post-vaccination IMNM was made due to the absence of other factors that may have led to the development of autoantibodies (medicines; e.g., statins, drugs) and the temporal relationship between exposure and event. This case report is the first to suggest that a COVID-19 vaccine may trigger anti-HMG-CoA reductase necrotizing myopathy.